Caffeine improves sperm quality, modulates steroidogenic enzyme activities, restore testosterone levels and prevent oxidative damage in testicular and epididymal tissues of scopolamine‐induced rat model of amnesia. (5th August 2019) - Akomolafe, Seun F.; Olasehinde, Tosin A.; Ogunsuyi, Opeyemi B.; Oyeleye, Sunday I.; Oboh, Ganiyu
Abstract: Objectives: This study was designed to assess the role of caffeine on fertility parameters in testicular and epididymal tissues of scopolamine‐induced model of amnesia in rats. Methods: Adult male rats were treated with scopolamine with or without caffeine. The modulatory effects of caffeine or scopolamine on fertility parameters were assessed in rats' testicular and epididymal homogenates. Key findings: Scopolamine‐induced sperm abnormalities, reduced steroidogenic enzyme 3β‐Hydroxysteroid dehydrogenase (3β‐HSD) and 17β‐Hydroxysteroid dehydrogenase (17β‐HSD) activities and serum testosterone levels in rats' testicular tissues. Treatment with caffeine increased 3β‐HSD and 17β‐HSD as well as testosterone levels. Caffeine also reversed sperm viability, sperm motility and sperm count in testicular tissues of scopolamine‐treated rats. Furthermore, scopolamine‐induced oxidative damage in rats' epididymal and testicular tissues via reduction of thiol and non‐protein thiol content as well as increase in reactive oxygen species (ROS) and malondialdehyde (MDA) levels. Caffeine attenuated oxidative stress in testicular and epididymal tissues of rats treated with scopolamine via increase in non‐protein and protein thiol levels with concomitant reduction in ROS and MDA levels. Conclusion: This study revealed that caffeine (5 and 25 mg/kg) improved sperm quality, increased steroidogenic enzyme activities and attenuated oxidative damage in testis and epididymis of rats treated with scopolamine.